Clinic application of tissue engineered bronchus for lung cancer treatment - Tan, Qiang; Liu, Ruijun; Chen, Xiaoke; Wu, Jingxiang; Pan, Yinggen; Lu, Shun; Weder, Walter; Luo, Qingquan (Journal of Thoracic Disease, 2017)
Background: Delayed revascularization process and substitute infection remain to be key challenges in tissue engineered (TE) airway reconstruction. We propose an “in-vivo bioreactor” design, defined as an implanted TE substitutes perfused with an intra-scaffold medium flow created by an extracorporeal portable pump system for in situ organ regeneration. The perfusate keeps pre-seeded cells alive before revascularization. Meanwhile the antibiotic inside the perfusate controls topical infection. Methods: A stage IIIA squamous lung cancer patient received a 5-cm TE airway substitute, bridging left basal segment bronchus to carina, with the in-vivo bioreactor design to avoid left pneumonectomy. Continuous intra-scaffold Ringer’s-gentamicin perfusion lasted for 1 month, together with orthotopic peripheral total nucleated cells (TNCs) injection twice a week. Results: The patient recovered uneventfully. Bronchoscopy follow-up confirmed complete revascularization and reepithelialization four months postoperatively. Perfusate waste test demonstrated various revascularization growth factors secreted by TNCs. The patient received two cycles of chemotherapy and 30 Gy radiotherapy thereafter without complications related to the TE substitute. Conclusions: In-vivo bioreactor design combines the traditionally separated in vitro 3D cell-scaffold culture system and the in vivo regenerative processes associated with TE substitutes, while treating the recipients as bioreactors for their own TE prostheses. This design can be applied clinically. We also proved for the first time that TE airway substitute is able to tolerate chemo-radiotherapy and suitable to be used in cancer treatment.